ASSESSING THE ROLE OF PHARMACISTS IN MANAGING CONTRAST MEDIA REACTIONS DURING RADIOLOGICAL PROCEDURES: A NURSING PERSPECTIVE - Abdulmajeed Khaled Al Anazi, Ahmed Hamed Hamid Almutairi, Ahmad Mohammad Al Farhoad, Mansour Ibrahim Mohammed Bin Hussein, Mohammed Mubarak Al Hasinah, Saeed Faiz Joyed Alaklabi, Sultan Mohammed Mousa Sadili, Yousef Mastour Al Anazi (Chelonian Research Foundation, 2024)
Contrast media reactions are a potential complication during radiological procedures, and effective management is crucial for patient safety. This study aimed to assess the role of pharmacists in managing contrast media reactions from the perspective of nursing staff. A cross-sectional survey was conducted among nurses working in radiology departments across multiple healthcare facilities. The survey evaluated nurses' experiences with contrast media reactions, their perception of pharmacists' involvement in managing these reactions, and the perceived benefits and challenges of pharmacist-nurse collaboration in this context. The survey results indicated that nurses frequently encounter contrast media reactions and value the expertise of pharmacists in managing these events. Nurses reported that pharmacists' involvement in patient assessment, medication selection, and monitoring contributes to improved patient outcomes and increased nursing confidence in managing reactions. However, challenges such as limited pharmacist availability and communication barriers were identified. The findings suggest that enhancing pharmacist-nurse collaboration and defining clear roles and protocols can optimize the management of contrast media reactions and improve patient safety in radiology departments.